Pulmonary adenofibroma - Wang Chen; Kang Liu; Yang Zhao; Chen-chen Liu; Meng-yu Cao; Xiao-juan Wang (Medicine, 2026)
Rationale: Pulmonary adenofibroma (PAF) is a rare, benign lung tumor, classified as a primary fibroepithelial tumor of the lung. Patient concerns: This study reports 3 cases of pulmonary adenofibroma (PAF). Case 1 was a solitary tumor presenting with a cough; Case 2 was a solitary tumor manifesting as chest tightness and pain; Case 3 was a multiple-lesion variant in an asymptomatic patient. Diagnoses: Pulmonary lesions were detected in all patients by computed tomography (CT) and were ultimately diagnosed as PAF through histopathological analysis. Interventions: Cases 1 and 2 underwent video-assisted thoracoscopic wedge resection, while Case 3 received conservative management with active surveillance. Outcomes: Cases 1 and 2 recovered well postoperatively, with no signs of recurrence or metastasis during follow-up. Case 3 remained stable, with some nodules demonstrating slow growth and no evidence of metastasis. Lessons: Pulmonary adenofibroma is readily confused with hamartoma and solitary fibrous tumor, and definitive diagnosis relies on histopathological examination.The tumor demonstrates indolent biological behavior and a favorable prognosis; therefore, overtreatment should be avoided in clinical practice.